2018
DOI: 10.1136/tobaccocontrol-2018-054518
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette explosion and burn injuries, US Emergency Departments 2015–2017

Abstract: There are more e-cigarette explosion and burn injuries in the USA than estimated in the past reports. Improved surveillance of e-cigarette injuries and regulation of e-cigarette devices is urgently needed. NEISS could be a valuable resource for e-cigarette injury surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 10 publications
6
42
0
2
Order By: Relevance
“…We observed the largest number of e-cigarette-related burn cases in 2016 followed by a decline in 2017, a similar observation as noted by Rossheim et al in their study on e-cigarette-related burn and explosion injuries presenting to EDs (7). The decline in the number of burn cases from 2016 to 2017 we observed was more pronounced than that reported by Rosseheim et al This decline coincided with the following events occurring around the time: (1) FDA provided an online education program entitled "Tips to Help Avoid "Vape" Battery Explosions" (16); (2) the U.S. Fire Department published a report of e-cigaretterelated res and explosions in the U.S. and provided information on appropriate use of e-cigarettes (17);…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed the largest number of e-cigarette-related burn cases in 2016 followed by a decline in 2017, a similar observation as noted by Rossheim et al in their study on e-cigarette-related burn and explosion injuries presenting to EDs (7). The decline in the number of burn cases from 2016 to 2017 we observed was more pronounced than that reported by Rosseheim et al This decline coincided with the following events occurring around the time: (1) FDA provided an online education program entitled "Tips to Help Avoid "Vape" Battery Explosions" (16); (2) the U.S. Fire Department published a report of e-cigaretterelated res and explosions in the U.S. and provided information on appropriate use of e-cigarettes (17);…”
Section: Discussionsupporting
confidence: 90%
“…Data from NPDS, a national surveillance system, indicate that approximately one-fth of e-cigaretterelated burn cases reported to PCCs were not referred to or did not arrive at HCFs. This information is complementary to the ndings from previous studies on e-cigarette-related burn injury cases presented to EDs (4,7) and is helpful in understanding the overall burden of e-cigarette-related burn injuries.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A study examining the frequency of explosions and burn injuries related to EC use found more than 2,000 cases from 2015 to 2017. 18 ECs are powered by lithium-ion batteries that can short circuit and explode. Multiple reasons can cause the malfunction of batteries, including improper charging and lack of fail-safe mechanisms.…”
Section: Explosions Battery Malfunction Injuriesmentioning
confidence: 99%
“…[14] A 2019 study on mice showed that the chronic use of e-cigarettes, with or without nicotine, damages the defence system of the lung, increasing lung susceptibility to virus and pathogens. [10] An additional hazard unique to e-cigarettes is the risk of explosion while being charged, used or even stored, [15,16] which has never been reported with traditional cigarettes. This has led to strict regulations that require these products to be carried in checked-in luggage only during air travel.…”
Section: The Case Against E-cigarettes E-cigarettes Are Not Harmlessmentioning
confidence: 99%